2009
DOI: 10.30535/mto.15.5.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Metrical Techniques of Flow in Rap Music

Abstract: This article systematically explores the concept of flow in rap music, with the goal of understanding how rappers’ uses of flow contribute both to the surface rhythmic vitality of a song and to deeper levels of musical meaning. I will explain the three most significant metrical techniques that constitute a rapper’s flow, and give examples of rap songs using each technique. The article concludes with some thoughts on how changes in flow as rap music evolved contributed not only to different style features, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 5 publications
0
36
0
Order By: Relevance
“…Later hip-hop, however, has considerably more freedom on all of the dimensions mentioned above (Adams, 2009). Walser (1995), for instance, gives a detailed analysis of Chuck D's 1988 performance in Fight the Power: this 'transitional' piece includes extensive mismatch between linguistic units and musical metrical ones, as well as certain types of non-linefinal rhyme; Walser offers some observations on how this marks a departure from earlier pieces.…”
Section: Hip-hopmentioning
confidence: 95%
See 3 more Smart Citations
“…Later hip-hop, however, has considerably more freedom on all of the dimensions mentioned above (Adams, 2009). Walser (1995), for instance, gives a detailed analysis of Chuck D's 1988 performance in Fight the Power: this 'transitional' piece includes extensive mismatch between linguistic units and musical metrical ones, as well as certain types of non-linefinal rhyme; Walser offers some observations on how this marks a departure from earlier pieces.…”
Section: Hip-hopmentioning
confidence: 95%
“…Although rhymes generally do occur at some more or less predictable rhythmic interval, they are not constrained to appear only in this position (Adams, 2009;Horn, 2010). And although perfect rhyme is frequent, imperfect rhyme is the rule: a previous version of the corpus with rhymes coded by listener intuition showed that about 65% of the perceived rhymes mismatched for one or more features/ segments.…”
Section: Hip-hopmentioning
confidence: 97%
See 2 more Smart Citations
“…However, writings on rap flows do exist: e.g. Adams (2008Adams ( , 2009aAdams ( and 2009b) (and a response to Adams [2008] in Williams [2009]), Krims (2000), Kautny (2009), Elflein (2009), Stougaard Pedersen (2009), Walser (1995). Also, the concept of flow plays a role in publications with a broader scope such as Rose (1994) and in particular Bradley (2009).…”
Section: Notesmentioning
confidence: 99%